استراتيجية الحجاج في المناظرة "مناظرة أبوجرّة سلطاني ورشيد بوجدرةأنموذجا" - منال سبيت (My University, 2023)
Abstract This study entitled "the strategies of argumentation in the debat which opposed" ABOU DJARA SOLTANI to RACHID BOUDJEDRA" is compased of two parts, the first theoretical" the argumentation and the literature of the debat" qs for the second part of this research, it was devated to the prarctice"the strategies of argumentation in the debat". The results obtained have been summarized in the conclusion the study also inclusion a list of bibliographical references related of subject. ------------------------ ملخص تُعالج هذه الدّراسة موضوعًا موسومًا بـ: " استراتيجيات الحجاج في المناظرة، مناظرة "أبو جرّة سلطاني ورشيد بوجدرة أنموذجا"، في فصلين؛ جاء الأوّل نظريا، موسوما بـ" الحجاج وأدب المناظرة" بينما عالج القسم الثاني والتطبيقي،"استراتيجيات الحجاج في المناظرة". كما ذُيل البحث بخاتمة تضمنت أهم النتائج المتوصل إليها، فضلا عن قائمة مصادر ومراجع ذات الصلة بالبحث -------------------- Résuém Cette étude intitulée les stratégies dˈ argumentation dans le debat qui a oppose "ABOU DJARA SOLTANI a RACHID BOUJDERA" les composée de deux parties la première théorique "lˈ argumentation est la littérature du débat" quand a la deuxième partie de cette recherche elle a été consacrée a la pratique " les stratégies de lˈ argumentation dans le debat". Les résulta obtenus ont été synthétises dans la conclusion étude comprend également une liste de références bibliographiques avant un rapport avec le sujet